A study on the structure formation and properties of noni juice microencapsulated with maltodextrin and gum acacia using single droplet drying. (March 2019) - Zhang, Chuang; Quek, Siew Young; Fu, Nan; Liu, Bin; Kilmartin, Paul A.; Chen, Xiao Dong
Abstract: Spray drying-based microencapsulation has been applied to mask unpleasant odours and to protect bioactives in liquid based products. However, little research has been undertaken to explore how particle formation occurs during the drying process and the relationships associated with particle properties. This study aimed to fill the gap by investigating the relation of structure formation and properties of microencapsulated fermented noni juice (FNJ) powder containing maltodextrin (M1, 10–13 DE; M3, 17–20 DE) and gum acacia (GA) using a single droplet drying (SDD) technique, mimicking the spray drying process. The impact of wall materials and solids content on the structure formation and particle properties including solubility, hygroscopicity, particle size, bulk density and microstructure were predicted. The SDD process was designed to observe the drying process and to investigate the morphological changes of semi-dried particles by attaching a water droplet or by suspending the semi-dried/dried particle in the drying chamber without air flow. Microscopic analysis show that microstructures of the particles were influenced by the wall materials. M3 particles showed the best solubility, and are predicted to have higher bulk density and hygroscopicity than M1 and GA particles. The M1 particles displayed good solubility and had a larger particle size than the M3 particles. Particles containing GA had the lowest dissolution rate, and are expected to have the lowest bulk density among the three wall materials. Overall, this research has provided insight into particle structure formation and the properties of microencapsulated FNJ powders by the above hydrocolloid materials. Graphical abstract: Image 1 Highlights: Structure formation and properties of fermented noni juice (FNJ) powder were revealed. Single droplet drying could be applied to study the above relationship. Microstructure and properties of FNJ powder was impacted by hydrocolloid used. Maltodextrin (10–13 DE) was predicted as a suitable carrier for encapsulating FNJ.